Assessment of CHF and Post-CHF Heat Transfer Models for High-Pressure Condition - Song, Meiqi; Liu, Xiaojing (Frontiers in Energy Research, 2021)
Supercritical heat transfer systems may undergo trans-critical procedures and work at subcritical conditions during startup, shutdown, or some accidents. However, well validated heat transfer models for the high-pressure condition (P/P_c>0.7) are still missing. In the present work, with exhaustive literature review, extensive experimental databanks of CHF and post-CHF heat transfer under high-pressure condition are established, respectively. Existing prediction models for the high-pressure condition are also summarized from all the world. Thereby, with the aid of the high-pressure experimental databank, prediction models get evaluated. It has been demonstrated that CHF correlations developed by Song et al. show good predictive capability, respectively. Post-dryout heat transfer could get well predicted by the Song correlation and the Bishop-1 correlation, respectively. Moreover, it is observed that as the pressure increases, CHF value drops but post-dryout heat transfer becomes better. Besides, according to literature review, so far, post-DNB heat transfer experiments for the high-pressure condition has not been carried out.